Role of patatin‐like phospholipase domain‐containing 3 on lipid‐induced hepatic steatosis and insulin resistance in rats. Issue 5 (25th January 2013) - Kumashiro, Naoki; Yoshimura, Toru; Cantley, Jennifer L.; Majumdar, Sachin K.; Guebre‐Egziabher, Fitsum; Kursawe, Romy; Vatner, Daniel F.; Fat, Ioana; Kahn, Mario; Erion, Derek M.; Zhang, Xian‐Man; Zhang, Dongyan; et al.
Abstract: Genome‐wide array studies have associated the patatin‐like phospholipase domain‐containing 3 (PNPLA3) gene polymorphisms with hepatic steatosis. However, it is unclear whether PNPLA3 functions as a lipase or a lipogenic enzyme and whether PNPLA3 is involved in the pathogenesis of hepatic insulin resistance. To address these questions we treated high‐fat‐fed rats with specific antisense oligonucleotides to decrease hepatic and adipose pnpla3 expression. Reducing pnpla3 expression prevented hepatic steatosis, which could be attributed to decreased fatty acid esterification measured by the incorporation of [U‐ 13 C]‐palmitate into hepatic triglyceride. While the precursors for phosphatidic acid (PA) (long‐chain fatty acyl‐CoAs and lysophosphatidic acid [LPA]) were not decreased, we did observe an ∼20% reduction in the hepatic PA content, ∼35% reduction in the PA/LPA ratio, and ∼60%‐70% reduction in transacylation activity at the level of acyl‐CoA:1‐acylglycerol‐sn‐3‐phosphate acyltransferase. These changes were associated with an ∼50% reduction in hepatic diacylglycerol (DAG) content, an ∼80% reduction in hepatic protein kinase Cε activation, and increased hepatic insulin sensitivity, as reflected by a 2‐fold greater suppression of endogenous glucose production during the hyperinsulinemic‐euglycemic clamp. Finally, in humans, hepatic PNPLA3 messenger RNA (mRNA) expression was strongly correlated with hepatic triglyceride and DAG content, supporting a potential lipogenic role of PNPLA3 in humans. Conclusion: PNPLA3 may function primarily in a lipogenic capacity and inhibition of PNPLA3 may be a novel therapeutic approach for treatment of nonalcoholic fatty liver disease‐associated hepatic insulin resistance. (HEPATOLOGY 2013)